2018
DOI: 10.1159/000488197
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Midregional Pro-Adrenomedullin and High-Sensitivity Troponin T Predict Perioperative Cardiovascular Events in Noncardiac Surgery

Abstract: Objective: We evaluated the utility of preoperative midregional (MR) pro-adrenomedullin (proADM) and cardiac troponin T (TnT) for improved detection of patients at high risk for perioperative cardiac events and mortality after major noncardiac surgery. Subjects and Methods: This prospective, single-center, observational study enrolled 79 patients undergoing major noncardiac surgery. After initial clinical assessment (clinical history, physical examination, echocardiogram, blood tests, and chest X-ray), MR-proA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 29 publications
(27 reference statements)
1
10
0
Order By: Relevance
“…Study Characteristics: A total of 7,877 participants were recruited in the eligible articles Among them three articles (Oscarsson et al, 2009b; Stone et al, 2014; Kopec et al, 2017) reported two biomarkers, eleven studies detected an association between BNP/ NT-proBNP and MACE (Feringa et al, 2007; Rajagopalan et al, 2008, 2011; Oscarsson et al, 2009a,b; Vetrugno et al, 2012; Cagini et al, 2014; Stone et al, 2014; Kim et al, 2016; Long et al, 2016; Kopec et al, 2017), fourteen reported an association between cTn and MACE (Lopez-Jimenez et al, 1997; Oscarsson et al, 2004, 2009b; Gibson et al, 2006; Ausset et al, 2008; Dawson-Bowling et al, 2008; Chong et al, 2009; Winkel et al, 2010; Biccard et al, 2012; Shroff et al, 2012; Gillmann et al, 2014; Kopec et al, 2017; Golubović et al, 2018; Kim et al, 2018), and four revealed a relationship between hs-CRP and MACE (Owens et al, 2007; Martins et al, 2011; Scrutinio et al, 2011; Stone et al, 2014; Table 1). The quality evaluation according to NOS of each selected article was also shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Study Characteristics: A total of 7,877 participants were recruited in the eligible articles Among them three articles (Oscarsson et al, 2009b; Stone et al, 2014; Kopec et al, 2017) reported two biomarkers, eleven studies detected an association between BNP/ NT-proBNP and MACE (Feringa et al, 2007; Rajagopalan et al, 2008, 2011; Oscarsson et al, 2009a,b; Vetrugno et al, 2012; Cagini et al, 2014; Stone et al, 2014; Kim et al, 2016; Long et al, 2016; Kopec et al, 2017), fourteen reported an association between cTn and MACE (Lopez-Jimenez et al, 1997; Oscarsson et al, 2004, 2009b; Gibson et al, 2006; Ausset et al, 2008; Dawson-Bowling et al, 2008; Chong et al, 2009; Winkel et al, 2010; Biccard et al, 2012; Shroff et al, 2012; Gillmann et al, 2014; Kopec et al, 2017; Golubović et al, 2018; Kim et al, 2018), and four revealed a relationship between hs-CRP and MACE (Owens et al, 2007; Martins et al, 2011; Scrutinio et al, 2011; Stone et al, 2014; Table 1). The quality evaluation according to NOS of each selected article was also shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…A study that defined MACE in a similar way to our study demonstrated the low accuracy and underestimation of MACE by RCRI and another specific risk model for vascular surgery [27]. Although we were not able to demonstrate the importance of individual markers in the prediction of postoperative cardiovascular events, in a recently published study, we showed the importance of midregional proadrenomedulin as a single predictive marker measured preoperatively [28, 29]. It is difficult to create a unique way of determining the risk score in patients preparing for major vascular surgery if a large number of events are followed in the postoperative course.…”
Section: Discussionmentioning
confidence: 44%
“…Our previous studies regarding the correlation between preoperative values of cardiac biomarkers and postoperative cardiovascular complications (including AF) did not show significant relationship between high preoperative values of single biomarker and cardiac complications. 24 -26 In this research we showed the importance of preoperative suPAR values in predicting the occurrence of paroxysmal AF 6 months after major vascular surgery.…”
Section: Discussionmentioning
confidence: 70%